2020
DOI: 10.3390/ijerph17103381
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Influence Mechanism of Green Utilization of Agricultural Wastes in Five Provinces of China through Farmers’ Motivation-Cognition-Behavior

Abstract: Using the theory of motivation, and the theory of planned behavior, this study establishes the “motivation-cognition-behavior” model of green utilization of agricultural waste from the perspective of farmers. In the motivational dimension, eight motivational factors were determined in three sub-dimensions of extrinsic motivation. In the cognitive dimension, three sub-dimensions of subjective norms, behavioral attitude, and perceived behavioral control are also determined. In the behavioral dimension, two sub-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The early scales of this theory were used to delineate and address dimensions such as customer expectations and expected value. In the extension of the theory of planned behavior, perceptual characteristics are associated with the willingness of the actor, i.e., perceptual characteristics are endogenously motivated to influence the subject's willingness to engage in activities, and there is a significant influence path between the two [42].…”
Section: User Levelmentioning
confidence: 99%
“…The early scales of this theory were used to delineate and address dimensions such as customer expectations and expected value. In the extension of the theory of planned behavior, perceptual characteristics are associated with the willingness of the actor, i.e., perceptual characteristics are endogenously motivated to influence the subject's willingness to engage in activities, and there is a significant influence path between the two [42].…”
Section: User Levelmentioning
confidence: 99%
“…Studies have shown that SE can promote the action of recycling at an individual level by influencing environmental behavior ( Bandura, 1977 , 1982 ; Ajzen, 2002 ). When faced with problems, individuals with greater SE tend to demonstrate positive aspects, thus promoting the development of the event toward success ( Tsiligianni et al, 2020 ; Yu et al, 2020 ). Therefore, in the construction of rural landscapes, villagers with stronger SE are often more willing to participate.…”
Section: Conceptual Model and Research Hypothesesmentioning
confidence: 99%
“…Green production cognition mainly includes environmental pollution cognition, economic development cognition, government policy understanding, and ecological knowledge. Studies have shown that farmers’ behavior is often determined by their cognitive ability [ 55 , 56 , 57 ]. The stronger the farmers’ green production cognitions, the higher the probability of converting green production intentions into actual behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%